A Role Based Access Control Using Cardinality Constraint Of Role Mining (International Journal of Advanced Research in Science, Management and Technology, 2015)
Role-based access control (RBAC) has long been recognized as a normative access control model. The essential notion of RBAC is to decouple users and permissions, and then associate both to roles respectively. This substantially simplifies the complexity of users and permissions management, widely perceived as onerous operations by system administrators. Employing RBAC is not only convenient but reduces the complication of access control since the number of roles in an organization is significantly smaller than that of users. Moreover, the use of roles as authorization subjects, instead of users, avoids having to revoke and re-grant authorizations whenever users change their positions and/or duties within the organization. As a result, RBAC has been implemented successfully by numerous information systems. The trend is that RBAC will maintain its increasing prevalence since the growing demand for cost-e activeness in management and security mechanism calls for it. Roles, users, permissions, objects and operations are constituents in RBAC where roles represent organizational agents that perform certain job functions within the organization, users are human beings and permissions are a set of many-to-many relations between objects and operations. According to the RBAC reference model, roles describe the relationship between users and permissions. Roles can be hierarchically structured, where senior roles generally inherit the permissions assigned to junior roles. Additionally, constraints such as separation of duties may be associated with the roles.
Keywords: RBAC, role mining, cardinality constraint, concurrent framework, post-processing framework